Determination of Radiation Hazard Arising from the 40-K Content of Bottled Mineral Water in Malaysia - Samat .S.B,; Evans .C.J, (Universiti Kebangsaan Malaysia, 2011)
Eleven different brands of mineral water available in Malaysia were assessed in comparison with two criteria for ingested radiation dose. It is concluded that mineral water can only contribute a very small fraction of the typical daily intake of potassium, and that the radiation dose acquired from any of the brands can never exceed a small fraction of the recommended limits.